Transformations of formulae of hybrid logic - Norgėla, Stanislovas; Petrauskas, Linas (Lietuvos matematikos rinkinys, 2010)
This paper describes a procedure to transform formulae of hybrid logic H(@) over transitive and reflexive frames into their clausal form.
Keywords: hybrid logic; clause